2003
DOI: 10.1051/0004-6361:20030646
|View full text |Cite
|
Sign up to set email alerts
|

ΛCDM and the distribution of dark matter in galaxies: A constant–density halo around DDO 47

Abstract: Abstract. In this paper we present a test case for the existence of a core in the density distribution of dark halos around galaxies. DDO 47 has a rotation curve that increases linearly from the first data point, at 300 pc, up to the last one, at 5 kpc. This profile implies the presence of a (dark) halo with an (approximately) constant density over the region mapped by data. This evidences the inability of standard Λ Cold Dark Matter scenario to account for the dark matter distribution around galaxies, and poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 24 publications
2
68
0
Order By: Relevance
“…A number of previous authors have reached similar conclusions (e.g., de Blok et al 2001aBlok et al , 2001bBorriello & Salucci 2001;de Blok & Bosma 2002;Salucci et al 2003;Simon et al 2003). We emphasize, however, that the observation that pseudoisothermal fits produce lower reduced 2 values than NFW or Moore profiles does not demonstrate the presence of a constant-density core.…”
Section: Nfw and Pseudoisothermal Fits To Rotation Curv Vessupporting
confidence: 82%
See 2 more Smart Citations
“…A number of previous authors have reached similar conclusions (e.g., de Blok et al 2001aBlok et al , 2001bBorriello & Salucci 2001;de Blok & Bosma 2002;Salucci et al 2003;Simon et al 2003). We emphasize, however, that the observation that pseudoisothermal fits produce lower reduced 2 values than NFW or Moore profiles does not demonstrate the presence of a constant-density core.…”
Section: Nfw and Pseudoisothermal Fits To Rotation Curv Vessupporting
confidence: 82%
“…Many authors have concluded that density profiles with constant-density cores fit the rotation curves of dwarf and LSB galaxies better than cuspy density profiles do (e.g., de Blok et al 2001aBlok et al , 2001bBorriello & Salucci 2001;de Blok & Bosma 2002;Salucci et al 2003;Simon et al 2003). Typical results from these studies are that the distribution of density profile slopes is ¼ 0:2 AE 0:2 (de Blok et al 2001ade Blok & Bosma 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution radio observations from spiral galaxies, along with their optical RC's, suggest that the dark matter is distributed in spherical haloes with nearly constant density cores (see [2,3,4] and references therein). On the other hand, theoretical predictions from the well known N-body ΛCDM simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While numerical results of the cold dark matter (CDM) model are remarkably successful in explaining the large scale structure of the universe, it encounters some problems at the scale of galactic or sub-galactic structures. For example, the numerical simulations usually predict cusped central halo density and too many sub-halos and small galaxies, which seem to be in contradiction with observations [2][3][4][5].Recently, there is a growing interest in the idea that DM particles are ultra-light scalars in Bose-Einstein condensate (BEC). (For a review, see Refs.…”
mentioning
confidence: 99%